Effects of monetary policy shocks on UK regional activity: A constrained MFVAR approach - Zeyyad Mandalinci (Queen Mary University of London, School of Economics and Finance, 2015)
This paper examines the effects of monetary policy shocks on UK regional economic growth and dispersion in a novel Constrained Mixed Frequency Vector Autoregressive framework. Compared to a standard MFVAR, the model partially accounts for missing quarterly observations for regional growth by exploiting national growth data. Results suggest significant heterogeneity in the importance of monetary policy shocks across regions. Mortgage indebtedness is highly related to regional sensitivity to monetary policy shocks. Also, there is some evidence suggesting that regions with larger share of manufacturing output and small and medium sized firms in employ ment are more sensitive to monetary policy shocks.
Keywords: E01; E3; E52; C11; C32; C5; 330; Regional growth; Monetary policy; Bayesian analysis; VAR; Mixed frequency data